Participation and Hindrances to Students’ Recreation at Selected Universities in Ondo State, Nigeria - Damilola Moronkeji B.; Dorcas Ayeni; Adebayo Emmanuel (Journal of Social and Development Sciences, 2022)
Recreation has several benefits, one of which is the health advantage that it brings to those who engage in it. Apart from being beneficial to health, one of the other benefits is in connection with good academic performance that it stimulates. This study focused on three selected public universities in Ondo State, Nigeria. It investigates the availability of recreational facilities, students' level of participation in recreational activities, and hindrances to students’ recreational participation in the selected universities. A purposive sample of 300 students was adopted and disaggregated into 106, 139 and 55 for the Federal University of Technology, Akure (FUTA), Adekunle Ajasin University, Akungba-Akoko (AAUA), and Ondo State University of Science and Technology, Okitipupa (OSUSTECH) respectively, using the relative population of students in the three universities. Data acquisition instruments included a questionnaire, interview and observation. The questionnaire administration involved a multi-stage sampling procedure that cumulated in obtaining data from the final-year students of each university's faculties and departments. Findings revealed that students' participation in recreation was at low ebb in the three universities with varying degrees of hindrances to participation across the institutions. Poor or absent facilities were the most dominant hindrance to recreation. The worst case was in OSUSTECH where the school authority did not provide any recreational facility on campus. Recommendations include sensitization programs to enlighten students on the need for recreation and the benefits of same to their health and educational pursuit; and upscaling of recreational facilities in the studied institutions.